Next-generation rotavirus vaccine developers meeting: Summary of a meeting sponsored by PATH and the bill & melinda gates foundation (19–20 June 2019, Geneva). Issue 52 (14th December 2020) - Fix, Alan; Kirkwood, Carl D.; Steele, Duncan; Flores, Jorge
Abstract: Despite the contribution of currently licensed live, oral rotavirus vaccines (LORVs) to alleviating the burden of severe disease and death from rotavirus gastroenteritis, those vaccines have proven less efficacious in resource-limited settings than in high- and middle-income countries. It has been proposed that the residual burden of rotavirus disease might be overcome with parenterally administered vaccines, or next-generation rotavirus vaccines (NGRV). To better define the progress of development of these vaccines, a meeting of vaccine developers and manufacturers engaged in NGRV research and development was convened in Geneva in June 2019. Several NRGVs are in various stages of preclinical development, and two have already entered clinical testing. The vaccine platforms include subunit protein, inactivated whole virus, virus-like particle and RNA-based vaccines. Meeting participants included groups involved in NGRV development, scientists investigating correlates of protection of rotavirus vaccines, and representatives of international organizations with insight into considerations for vaccine introduction. This report summarizes the presentations shared at the meeting.